Omslag van 'Jan Trip Jan Tree en andere verhalen'. Nienke van Hichtum is het pseud. van S. Troelstra Bokma de Boer
Omslag van 'Jan Trip Jan Tree en andere verhalen'. Nienke van Hichtum is het pseud. van S. Troelstra Bokma de Boer.